logo

Ask Questions, Get Answers

 
X
 Search
Want to ask us a question? Click here
Browse Questions
Ad
Home  >>  CBSE XII  >>  Math  >>  Model Papers
0 votes

Prove that \( \cos^{-1}(4x^3-3x)=3\cos^{-1}x.\)

Can you answer this question?
 
 

1 Answer

0 votes
Tool Box:

\[Take\:x=CosA\:then\:Cos^{-1}x=A\]

\[L.H.S.\:becomes.Cos^{-1}Cos3A=3A=3Cos^{-1}x\]
answered Feb 15, 2013 by rvidyagovindarajan_1
 

Related questions

Ask Question
student study plans
x
JEE MAIN, CBSE, NEET Mobile and Tablet App
The ultimate mobile app to help you crack your examinations
Get the Android App
...